Age‐dependent deterioration of locomotion in Drosophila melanogaster deficient in the homologue of amyotrophic lateral sclerosis 2. (7th April 2014) - Takayama, Yuta; Itoh, Reina E.; Tsuyama, Taiichi; Uemura, Tadashi; Hayashi, Shigeo
<x xml:space="preserve">Abstract</x> Recessive mutations in the amyotrophic lateral sclerosis 2 (ALS2) gene have been linked to juvenile‐onset ALS2. Although one of the molecular functions of the ALS2 protein is clearly the activation of Rab5, the mechanisms underlying the selective dysfunction and degeneration of motor neurons in vivo remain to be fully understood. Here, we focused on the ALS2 homologue of Drosophila melanogaster, isolated two independent deletions, and systematically compared phenotypes of the mutants with those of animals in which Rab5 function in identified neurons was abrogated. In the dALS2 mutant flies, we found that the stereotypic axonal and dendritic morphologies of neurons shared some features with those in Rab5‐deficient flies, but the dALS2 mutant phenotypes were much milder. We also found that the abrogation of Rab5 function in motor neurons strongly depressed the locomotion activity of adults, resembling the behavior of aged dALS2 mutants. Importantly, this age‐dependent locomotion deficit of dALS2 mutants was restored to normal by expressing the dALS2 transgene in a wide range of tissues. This finding provided a platform where we could potentially identify particular cell types responsible for the phenotype by tissue‐specific rescue experiments. We discuss our results and the future usage of the dALS2 mutant as a new ALS model.